Anti-tuberculosis treatment defaulting: an analysis of perceptions and interactions in Chiapas, Mexico Abandono del tratamiento antituberculosis: un análisis de percepciones e interacciones en Chiapas, México - Ivett Reyes-Guillén; Héctor Javier Sánchez-Pérez; Jorge Cruz-Burguete; Miren Izaurieta-de Juan (Instituto Nacional de Salud Pública, 2008)
OBJECTIVE: To analyze the perceptions and interactions of the actors involved in anti-tuberculosis treatment, and to explore their influence in treatment defaulting in Los Altos region of Chiapas, Mexico. MATERIAL AND METHODS: From November 2002 to August 2003, in-depth interviews were administered to patients with PTB, patients' family members, institutional physicians, community health coordinators, and traditional medicine practitioners. RESULTS: We found different perceptions about PTB between patients and their families and among health personnel, as well as communication barriers between actors. Defaulting is considered to be mainly due to the treatment's adverse effects. CONCLUSIONS: It is necessary to conduct research and interventions in the studied area with the aim of changing perceptions, improving sensitization, quality and suitability of management of patients with PTB in a multicultural context, and promoting collaboration between institutional and traditional medicine. OBJETIVO: Analizar percepciones e interacciones entre actores involucrados en el tratamiento antituberculosis y su influencia en el abandono del tratamiento en los Altos de Chiapas, México. MATERIAL Y MÉTODOS: De noviembre 2002 a agosto 2003, se realizaron entrevistas a profundidad a pacientes con TBP, familiares, médicos institucionales, coordinadores comunitarios de salud y médicos tradicionales. RESULTADOS: Se encontraron diferentes percepciones entre los pacientes y sus familiares, respecto a las del personal de salud, así como barreras de comunicación entre los distintos actores. Los efectos adversos del tratamiento antituberculosis, son consideradas como una de las principales causas de su abandono. CONCLUSIONES: Es necesario que en la región estudiada se realicen investigaciones e intervenciones encaminadas a: cambiar percepciones y mejorar la sensibilidad, calidad y adecuación del manejo de pacientes con TBP en contextos multiculturales, así como impulsar el trabajo conjunto entre la medicina institucional y tradicional.